2020
DOI: 10.3390/cells9061484
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Nuclear NOTCH2 by Gliotoxin Recovers a Tumor-Suppressor NOTCH3 Activity in CLL

Abstract: NOTCH signaling represents a promising therapeutic target in chronic lymphocytic leukemia (CLL). We compared the anti-neoplastic effects of the nuclear NOTCH2 inhibitor gliotoxin and the pan-NOTCH γ-secretase inhibitor RO4929097 in primary CLL cells with special emphasis on the individual roles of the different NOTCH receptors. Gliotoxin rapidly induced apoptosis in all CLL cases tested, whereas RO4929097 exerted a variable and delayed effect on CLL cell viability. Gliotoxin-induced apoptosis was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 69 publications
(133 reference statements)
0
8
0
Order By: Relevance
“…In the circulation system, NOTCH2 is involved in the regulation of FCER2 expression in chronic lymphocytic leukemia (Schwarzmeier et al, 2005), whereas gliotoxin induces the apoptosis by inhibiting the NOTCH2/FCER2 signaling axis (Hubmann et al, 2013(Hubmann et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the circulation system, NOTCH2 is involved in the regulation of FCER2 expression in chronic lymphocytic leukemia (Schwarzmeier et al, 2005), whereas gliotoxin induces the apoptosis by inhibiting the NOTCH2/FCER2 signaling axis (Hubmann et al, 2013(Hubmann et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we found that NOTCH2 signaling was activated in human SSC line by FCER2 overexpression. In the circulation system, NOTCH2 is involved in the regulation of FCER2 expression in chronic lymphocytic leukemia (Schwarzmeier et al, 2005), whereas gliotoxin induces the apoptosis by inhibiting the NOTCH2/FCER2 signaling axis (Hubmann et al, 2013, 2020). NOTCH2 has been shown to be involved in regulation of the proliferation, migration, and invasion of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The main research of BCL6 is focused on lymphoma and it was considered as a therapeutic target ( Leeman-Neill & Bhagat, 2018 ). FCER2 (CD23) surface expression is mutually exclusive in chronic lymphocytic leukemia (CLL) ( Hubmann et al, 2020 ). Moreover, the role of DENND6B, NCOA7and TMCO6 in cancer is largely unknown, our results indicated their important role in colorectal cancer; further studies are expected to reveal their biological function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression levels of antiapoptotic Bcl-2 and caspase-8 decreased, whereas expression levels of BAK, BAX, BID, and caspase-3 were significantly increased in both A549 and L132 cells, suggesting gliotxin induce the apoptosis of A459 and L132 cells via the activation of caspases and the Bax pathway, also implicating mitochondrial damage [47]. Gliotoxin can also induce the apoptosis of chronic lymphocytic leukemia cells (CLLs) (IC 50 between 0.1 and 1 µM), associated with the inhibition of the NOTCH2/FCER2 (CD23) axis, together with the upregulation of the NOTCH3/NR4A1 axis and NF-κB factor [87,88], thus providing a novel strategy for the treatment of CLLs. In addition, gliotoxin can also induce apoptosis via the deregulation of NOTCH2 mRNA expression towards cell lines derived from melanoma (518A2), hepatocellular carcinoma (SNU398, HCC-3, Hep3B), and pancreas carcinoma (PANC1) with the high expression level of NOTCH 2 ; the apoptotic effect was not observed in the NOTCH-negative cell line Huh7 [87], suggesting the vital role of NOTCH in gliotoxin-inducing apoptosis.…”
Section: The Induction Of Cell Apoptosismentioning
confidence: 99%